PROBLEMATIKA PERKAWINAN DI BAWAH UMUR PADA MASA PANDEMI COVID-19 DI DESA BENGKEL - HERY ZARKASIH; NOVITA LISTYANINGRUM (GANEC SWARA, 2023)
The number of cases of child marriage in West Lombok Regency experienced a significant increase during the Covid-19 period. From January to July 2020, 15 percent of cases of child marriage were recorded from 5,000 marriages. There are many cases of child marriage in Bengkel Village, Labuapi District, West Lombok Regency. This study aimed to analyze the problems of implementing marriage during the Covid-19 pandemic in Bengkel Village. Meanwhile, the research method used is empirical legal research. The results showed that the issues of implementing child marriage that occurred in Bengkel Village during the Covid-19 pandemic, namely that 2 couples wanted to carry outchild marriage, and 1 couple was prevented by the village by involving the KPAI so that the wedding did not take place. Meanwhile, another couple persisted in continuing their wedding because they did not violate religious or customary provisions. Several factors cause child marriage in Bengkel Village, namely education, economics, and habits. One of the efforts that can be made to overcome these factors is to cooperate with the courts, police, Babin, KPAI, KB, heads of departments, and heads of local hamlets to conduct outreach to underage children in the area.